Odonates, gregarines and water mites: why are the same host species infected by both parasites?. (15th May 2018) - Ilvonen, Jaakko J.; Kaunisto, Kari M.; Suhonen, Jukka
Abstract : 1. Damselflies and dragonflies are widely parasitised insects and numerous studies have tried to understand this host–parasite relationship. However, most of these studies have concentrated on a single host species, neglecting the larger pattern within the Odonata order. 2. The aim of this paper was to examine different damselfly and dragonfly species for common endo‐ and ectoparasites and whether a general infection pattern can be found. Additionally, the goal was to investigate whether the phylogeny of the host species could explain these possible infection patterns. To this end, a dataset from the existing literature was compiled and the prevalence of endoparasitic gregarines and ectoparasitic water mites was analysed for 46 different odonate species. 3. Three distinct patterns were found: (i) most of the odonate host species had both gregarines and water mites, rather than only either one or neither; (ii) there appears to be a positive association between gregarine and water mite prevalences across host species; (iii) a weak phylogenetic signal was detected in gregarine prevalence and a strong one in water mite prevalence. 4. It is hypothesised that, due to the infection and transmission mechanisms by which water mites and gregarines infect different odonate host species, parasitism is aggregated to common, high‐density species. However, much research is needed in order to fully understand this relationship between odonates and their parasites, especially within the same host populations and host species assemblages. Abstract : Most of the odonate species in our study were parasitised by both gregarines and water mites. There appears to be a positive association between water mite and gregarine parasitism across the odonate species. A weak phylogenetic signal was detected in gregarine prevalence and a strong one in water mite prevalence.